Mental health difficulties among trans and gender diverse young people with an autism spectrum disorder (ASD): Findings from Trans Pathways. (May 2021) - Strauss, Penelope; Cook, Angus; Watson, Vanessa; Winter, Sam; Whitehouse, Andrew; Albrecht, Nicole; Wright Toussaint, Dani; Lin, Ashleigh
Abstract: Recent research highlights an overlap of gender diversity and autism spectrum disorders (ASD); however, data on individuals who are trans and also on the autism spectrum are largely from clinical samples and may not be representative of individuals who are trans with ASD in the general population. In addition, there is scant literature on the mental health of these individuals and their experiences in accessing gender-affirming care. We investigated the prevalence of ASD in trans young people, their mental health (psychiatric diagnoses and self-harm and suicidal behaviors) and experiences in accessing gender-affirming care. This is an analysis of data collected in an Australian cross-sectional mixed methods survey (N = 859) of trans young people aged 14–25 years. Overall, 22.5% of participants had ever received a diagnosis of ASD from a health professional. This group was more likely to exhibit current psychopathology, have engaged in self-harming and suicidal behaviors, and was also more likely than the non-ASD diagnosed reference group to have received a psychiatric diagnosis. The ASD-diagnosed group were also more likely to experience barriers in accessing gender-affirming care. This is the first large population-based sample of trans individuals with ASD to report on mental health outcomes and experiences in accessing gender-affirming care. We highlight the necessity for clinicians working with either trans or ASD populations to have awareness of the co-occurrence, and to cultivate skills to work with individuals who are both trans and on the autism spectrum. Highlights: The prevalence of ASD within this sample of trans young people is 22.5%. Young people who are both trans and have ASD are at high risk for mental health issues. Improved support of trans individuals on the autism spectrum is needed.